(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the role and importance of human security in the mythological religious philosophy. Mythological - religious and pagan beliefs arising concentrated knowledge about the safety and successfully served as protection to ensure the safety and continuity of personal and social existence. Security laws, certain supernatural life - mythical creatures, the divine genealogy, united by God. Observance of rituals ensures the security, peace and stability provides a static essence, and the guarantor of stability was the natural rational, eternal, divine number for things instilled in the minds of ancient people. In ancient times, podiums feel safe only in unity with nature, as «living in nature» and developed his subjective ability in harmony with the volume projective reality. Feature Article - Today in the philosophical science is very important to carefully consider the essence of the concept of «security. Keywords: security, philosophy, religion, myth, values.